POSHAN’s abstract digest on maternal and child nutrition research - Issue 46 - Avula, Rasmi (International Food Policy Research Institute, 2022)
Issue 46 of the POSHAN Abstract Digest brings to you yet another collection of articles on various maternal and child nutrition topics. This issue features studies on the prevalence and impact of anaemia in adolescents, an ecological analysis of child undernutrition and overweight, micronutrient supplementation and linear growth, diets, diet quality, and dietary diversity. growth. This issue also include two studies- one on cost-consequence analyses and another on the process evaluation-based on nutrition-sensitive agriculture interventions implemented in Odisha to improve maternal and child health nutrition. Other interesting studies included in this issue are on birthweight data quality, decentralization in the Integrated Child Development Services, use of digital technology to improve service delivery, and changes to service delivery in multiple states across India during COVID-19.